Extreme battlefields : when war meets the forces of nature - Kyi, Tanya Lloyd, 1973- (Annick Press, 2016)
"This non-fiction book for 10-14 year olds explores the ways the environment--the weather, climate, or geography--influences the outcomes of wars. The historical examples examined are: Hannibal in the Alps, the US Navy during Typhoon Cobra (WWII), the Canadian Army in Passchendaele (WWI), the dispute between India and Pakistan over the Siachen Glacier, the Battle of Pichincha (a volcano), General Wei Qing vs the Xiongnu in the Gobi Desert, the US Army in Vietnam, Napoleon's defeat in Russia, and the Battle of Tora Bora"--